2020
DOI: 10.1111/apa.15495
|View full text |Cite
|
Sign up to set email alerts
|

Review of guidelines and recommendations from 17 countries highlights the challenges that clinicians face caring for neonates born to mothers with COVID‐19

Abstract: Aim: This review examined how applicable national and regional clinical practice guidelines and recommendations for managing neonates born to mothers with COVID-19 mothers were to the evolving pandemic. Methods: A systematic search and review identified 20 guidelines and recommendations that had been published by May 25, 2020. We analysed documents from 17 countries: Australia,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
79
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 74 publications
(86 citation statements)
references
References 54 publications
0
79
0
7
Order By: Relevance
“…more commonly acquired postnatally, through environmental exposure. There are wide differences in this matter between the clinical guidelines issued by scientific societies and authorities worldwide 96 (https://www.cdc.gov/coronavirus/2019-ncov/hcp/ caring-for-newborns.html, https://www.rcog.org.uk/globalassets/ documents/guidelines/2020-06-04-coronavirus-covid-19-infectionin-pregnancy.pdf) and these have been recently highlighted 97 . Thus, we believe that a correct and complete counselling should be given to families in order to allow a well-informed choice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…more commonly acquired postnatally, through environmental exposure. There are wide differences in this matter between the clinical guidelines issued by scientific societies and authorities worldwide 96 (https://www.cdc.gov/coronavirus/2019-ncov/hcp/ caring-for-newborns.html, https://www.rcog.org.uk/globalassets/ documents/guidelines/2020-06-04-coronavirus-covid-19-infectionin-pregnancy.pdf) and these have been recently highlighted 97 . Thus, we believe that a correct and complete counselling should be given to families in order to allow a well-informed choice.…”
Section: Discussionmentioning
confidence: 99%
“…If rooming-in is chosen, appropriate hygiene advice and personal protective equipment should be given, as these may significantly reduce the risk of transmission 99 . Hygiene measures during mother-neonate contact were described inconsistently and only in a minority of articles 23,24,34,39,64,67,75 , and, given the differences in guidelines worldwide 97 , dedicated studies are warranted to understand what would be the ideal equipment and policy to be applied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the start of the pandemic, there has been an exponential increase in publications describing the measures that need to be taken in specific patient groups and this has resulted in various, and often diverse, proposals for guidelines [8]. Unfortunately, at the time of writing, there is no universally applicable, evidence-based guideline for the prevention and management of COVID-19 infection in the paediatric population,.…”
mentioning
confidence: 99%
“…These studies found that the recommendations formulated within the CPGs were lacking evidence and that the overall quality of CPGs was poor and variable [11][12][13]. However, these studies are limited in that they assessed CPGs published very soon after the rst con rmed case of COVID-19 [11], CPGs addressing very speci c interventions [12], or CPGs with very speci c populations [13]. To our knowledge, this study will be the rst to assess the quality of evidence-based CPGs focused on the use of TIs and/or management of COVID-19.…”
mentioning
confidence: 99%